(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
The Gross Domestic Product (GDP) in Uzbekistan expanded 6.40 percent in the second quarter of 2024 over the same quarter of the previous year. GDP Annual Growth Rate in Uzbekistan is expected to be 6.20 percent by the end of this quarter, according to Trading Economics global macro models and analysts expectations.In this article, the comparison of various models related to macroeconomic balance and economic growth is studied on the basis of various graphs, formulas and tables, and their comparisons are made. In addition, the specific characteristics of the models and their application in what period and for what economic systems are covered in detail. Economic growth refers to an increase in the size of a country’s economy over a period of time. The size of an economy is typically measured by the total production of goods and services in the economy, which is called gross domestic product (GDP).